Transport Corridors and Their Wider Economic Benefits : A Critical Review of the Literature - Roberts, Mark; Melecky, Martin; Bougna, Theophile; Xu, Yan Sarah (World Bank, Washington, DC, 2018)
Transport corridors can generate wider economic benefits and costs through their effects on a potentially diverse set of development outcomes, such as economic growth, poverty, jobs, equity, environmental quality, and economic resilience. To advance understanding of how corridors could generate wider economic benefits, this paper undertakes a quantitative review of the literature that estimates the economic benefits of large transport infrastructure projects. It conducts a meta-analysis of 234 estimated impacts found in 78 studies. It focuses on roads, rails, and waterways because transport corridors based on these modes have clearer potential for economic spillovers than, for example, airline routes. The conceptual structure for the review is guided by a simple canonical model describing the policy maker's problem in maximizing the net wider economic benefits of corridors. The meta-analysis confirms that characteristics of individual studies, as well as the placement and design of the transport infrastructures systematically influence the findings of the corridor studies. It also shows that, on average, estimated impacts of corridor interventions on economic welfare and equity tend to be beneficial, while they are often detrimental for environmental quality, and possibly also for social inclusion. Because, around this average, impacts vary widely, policy makers could use complementary policies and institutions to mitigate potential trade-offs and support losers. To clarify the nature and extent of these trade-offs and varied impacts across locales and population groups, much more research is required.